Intensive ketamine use for multiple years: A case report. (January 2015) - Liu, James X.; Zerbo, Erin; Ross, Stephen
<x xml:space="preserve">Abstract</x> Ketamine is known within the medical field for its anesthetic properties, yet its unique psychedelic and antidepressant properties are being increasingly recognized. We document the case of a patient with bipolar I disorder and an extensive history of substance dependence who used large doses of ketamine (1–3 g) on a daily basis over a period of 5 years, and described acute antidepressant effects as well as diminished cravings for alcohol. While his use was untenable and ultimately led to an inpatient admission, it is notable that he did not experience a withdrawal syndrome nor did he have any observable cognitive deficits upon cessation of use. Such a unique drug profile suggests that further exploration of its risks and therapeutic potential in treating mood and addiction disorders is warranted. (Am J Addict 2015;24:7–9)